The Role of Technology in Internal Oversight of Public Administration: Improving Efficiency and Transparency - Manik, Fitriyani; Rengifurwarin, Rengifurwarin; Madubun, Madubun (MSJ : Majority Science Journal, 2024)
The development of information technology has had a significant impact in various sectors, including internal supervision of public administration. This study aims to examine the role of technology in improving the efficiency and transparency of public administration supervision. The method used in this study is Systematic Literature Review (SLR), which aims to explore various technology applications that can support internal supervision, such as cloud-based management systems, data-based audit applications, and the application of blockchain technology to maintain data integrity. The results of the study show that the application of technology can reduce the potential for abuse of power, increase accountability, and accelerate the decision-making process in the management of public administration. Technology also contributes to creating a more transparent and effective surveillance system, making it easier for the public to access information, and speeding up the identification of problems. This research makes an important contribution to the understanding of the role of technology in strengthening good public governance, with the hope of improving the quality and efficiency of public administration through the proper use of technology.